Time Domain Response of Uniform RC Lines With Resistive Termination at Both Ends - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
The time domain response of uniform RC lines with resistive termination at both ends is obtained by obtaining the approximate poles of the transfer function. A simple model is developed for the URC line. The model consists of three passive elements only and can be easily implemented for computeraided analysis of URC lines with resistive termination at both ends.